Foraminifera from Late Pliocene sediments of Heidemann Valley, Vestfold Hills, East Antarctica - Quilty, PG (2010)
The foraminiferal fauna in Pliocene (3.5-2.6 Ma) sediments excavated in a trench 4 m deep, in Heidemann Valley, Vestfold Hills, East Antarctica is examined and described. Sediments accumulated in shallow, fully marine conditions in a glacial valley during the last major glacial event in the Vestfold Hills. The section correlates well with the Cockburn Island Formation (Pecten Conglomerate), sediments of Wright Valley, Dry Valleys, and marine event M10 recognized as far south as Amery Oasis, 500 km to the southwest of Heidemann Valley. The foraminiferal fauna generally is dominated by infaunal cassidulinid and elphidiid species. Assemblages vary dramatically, even between samples collected very close to each other, and no simple relationship with the position in sections or the valley can be determined. It is a shallow-water, fully marine fauna virtually free of agglutinated forms and with a low planktonic component Planoglabratella webbi is described as new.